2021
DOI: 10.1002/er.7558
|View full text |Cite
|
Sign up to set email alerts
|

Process development and performance assessment of flexible calcium looping biomass gasification for production of renewable gas with adjustable composition

Abstract: Summary In recent years, the field of biomass gasification as a method of transforming biomass into a more useable gaseous fuel experienced expedited development since it represents a prominent way to achieve sustainability goals and targets set by the Paris accord and, more recently, the European Green Deal. The use of natural gas is projected to reduce with the transition toward exploitation of renewable gas, while a new area of hydrogen applications is also emerging. However, with uncertain production of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Pyrolysis/gasification creates a synthetic gas that regenerates long-chain carbon biofuel on the basis of Fischer-Tropsch technology. Coupled with advanced technologies such as calcium looping for carbon capture [85], this technology can provide a facile way of producing cleaner alternatives to traditional fossil fuels (e.g., synthetic methane). On the other hand, biochemical conversion relies on microorganisms and enzymes to convert cellulose and hemicellulose and reduce sugar.…”
Section: Biofuelsmentioning
confidence: 99%
“…Pyrolysis/gasification creates a synthetic gas that regenerates long-chain carbon biofuel on the basis of Fischer-Tropsch technology. Coupled with advanced technologies such as calcium looping for carbon capture [85], this technology can provide a facile way of producing cleaner alternatives to traditional fossil fuels (e.g., synthetic methane). On the other hand, biochemical conversion relies on microorganisms and enzymes to convert cellulose and hemicellulose and reduce sugar.…”
Section: Biofuelsmentioning
confidence: 99%
“…hydrogen production [11], and synthesis of chemicals, such as dimethyl ether [16] and synthetic natural gas [20].…”
Section: Introductionmentioning
confidence: 99%
“…Carbonate looping (CaL), which considers natural sorbents such as limestone, has been proven to be a viable process for reducing CO 2 emissions from power generation and hydrogen production technologies. 11 Shimizu et al 12 demonstrated that the CFPP retrofitted with CaL resulted in 1.4% points lower efficiency penalty than oxyfuel combustion. Romeo et al 13 demonstrated that the CaL retrofit to a 450 MW el CFPP would reduce the net efficiency of the host plant by 7.9% points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation